Analysis Of International Law on Extradition Treaties Between Countries In Indonesia: A Juridical Review - Ahya Aditya N Faizal (Cita konsultindo, 2025)
Interstate extradition treaties are a key instrument in addressing these complexities, although diplomatic challenges often influence their decisions. This research aims to examine and understand the international legal perspective on interstate extradition treaties in Indonesia. This research uses a normative juridical method and a qualitative descriptive approach to explore international legal perspectives on extradition. Legal materials are collected through literature study and analyzed qualitatively to reach an in-depth conclusion regarding this phenomenon. An analysis of international law regarding interstate extradition treaties in Indonesia shows that extradition is an important mechanism for law enforcement involving international cooperation, governed by bilateral or multilateral treaties and principles of international law. Indonesia, through Law No. 1/1979, regulates extradition processes that require specific treaties, while also considering aspects such as human rights and state sovereignty in extradition requests. In addition, Indonesia also regulates extradition by formal treaties with various countries as well as through national legislation, which includes important principles such as reciprocity, non-extradition for political crimes, and the obligation to refuse extradition of citizens.